COMORBIDITY IN RHINOSINUSITIS AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE: CLINIC AND TREATMENT FEATURES - Kh. O. Saliahunova, Saliahunova Khurshidakhon Odilovna (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, special attention is paid to the clinic, diagnosis and treatment of comorbid processes in diseases of the nasal cavity and diseases of the bronchopulmonary system. The fact that such comorbid pathologies are becoming more common in recent years has raised the question that patients negatively affect their quality of life.